ASSOCIATION OF SINO-RUSSIAN TECHNICAL UNIVERSITIES AS A NEW INSTITUTION FOR INTERNATIONAL COOPERATIONIN HIGHER EDUCATION AREA - Sergey V. Korshunov; Mikhail V. Kuznetsov; Victor B. Timofeev (Moscow Polytechnic University, 2016)
Russian Federation and China have been involved into a longAstanding partnership and cooperation for decades. Both countries rely on advanced technological development and modernization of the educational system. The acknowledged instrument for cooperation in higher education is represented by professional university associations. Association of SinoARussian Technical Universities (ASRTU) established in 2011 features one of the first RussianAChinese associations in engineering training. Within a short period of time the association has confirmed its role as a new institution to join together efforts of the two nations in the evolution of higher education. The article deals with the history and the main activity areas of the ASRTU, and it also summarizes work undertaken since its creation in 2011.